2020
DOI: 10.1007/s11265-019-01511-3
|View full text |Cite
|
Sign up to set email alerts
|

An End-to-End Approach to Automatic Speech Assessment for Cantonese-speaking People with Aphasia

Abstract: Conventional automatic assessment of pathological speech usually follows two main steps: (1) extraction of pathology-specific features; (2) classification or regression on extracted features. Given the great variety of speech and language disorders, feature design is never a straightforward task, and yet it is most crucial to the performance of assessment. This paper presents an end-to-end approach to automatic speech assessment for Cantonese-speaking People With Aphasia (PWA). The assessment is formulated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The CNs is effective to improve robustness of embedding representations of ASR output and thus improving the assessment performance. We follow the approach in [11] to develop an end-to-end assessment system. With the same arrangement of 5-fold cross validation on 92 impaired speakers, a CNN model with global average pooling is trained with Log-Mel acoustic features from PWA speech.…”
Section: Speaker-level Classification Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The CNs is effective to improve robustness of embedding representations of ASR output and thus improving the assessment performance. We follow the approach in [11] to develop an end-to-end assessment system. With the same arrangement of 5-fold cross validation on 92 impaired speakers, a CNN model with global average pooling is trained with Log-Mel acoustic features from PWA speech.…”
Section: Speaker-level Classification Accuracymentioning
confidence: 99%
“…Generally speaking, use of expert knowledge in feature design and extraction played an important role in most previous studies on automatic assessment of language impairment. Recently, we attempted an end-to-end approach to the problem, in which a direct mapping from conventional acoustic features (i.e., Log-Mel filter-bank features) to assessment score was realized with a Convolutional Neural Network (CNN) model [11]. By visualizing the learned features using class activation mapping [12], it was confirmed that the CNN model could capture impairment-related acoustic characteristics that are in agreement with human-designed features.…”
Section: Introductionmentioning
confidence: 98%
“…Speech assessment is used extensively in the diagnosis of Parkinson’s and aphasia diseases [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Aphasia is an acquired neurogenic language disorder that can be evaluated with one of the well-known assessment tools, such as the Chinese Rehabilitation Research Center Aphasia Examination (CRRCAE [ 15 ], for Chinese-dialect-speaking patients), the Aachen Aphasia Test (AAT [ 16 ], for German-speaking patients) and the Boston Diagnostic Aphasia Examination (BDAE [ 17 ], for English-speaking patients).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, there are three aphasia assessment tasks whereby an SLP performs a comprehensive examination of the patient’s communication abilities, including speaking, expressing ideas, understanding language, reading, and writing. These tasks are the discrimination between normal and aphasic speech [ 9 ], the assessment of the degree of severity of impairment for aphasic patients [ 10 , 12 ], and the classification of aphasia syndromes (such as Global aphasia, Broca’s aphasia, Wernicke’s aphasia and amnesic aphasia) [ 13 , 14 ]. Conventional methods of aphasia assessment and rehabilitation are resource-intensive processes that require the presence of an SLP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation